Calcium uptake and release modulated by counter-ion conductances in the sarcoplasmic reticulum of skeletal muscle - Fink, Rainer; Veigel, Claudia (Acta physiologica Scandinavica, 1996)
The sarcoplasmic reticulum (SR) plays the central role in regulating the free myoplasmic Ca2+ level for the contractile activation of skeletal muscle. The initial stages of the voltage-controlled Ca2+ release mechanism are known in molecular detail. However, there is still very little known about the later stages of Ca2+ uptake and total Ca2+ turnover in the contraction-relaxation cycle under normal physiological conditions or under conditions influenced by fatigue or disease. Ca2+ uptake and release are both accompanied by ‘counter-ion’ movements across the SR membrane which prevent or reduce the generation of SR membrane potentials and balance for electroneutrality in the SR lumen. The SR membrane is permeable for the cations K+, Na+, H+ and Mg2+ and the anion Cl-. Using electron-probe X-ray microanalysis, it has been shown that during tetanic stimulation the Ca2+ release was mainly balanced by uptake of K+ and Mg2+, leaving a charge deficit that was assumed to be neutralized via H+ ion or organic counter-ion movement. The low time resolution of electron-probe X-ray microanalysis leaves the possibility of other transient concentration changes in the SR, e.g. for Cl- ions. Possible physiological roles of the SR counter-ion conductances can be tested using skinned muscle fibre preparations with intact sarcoplasmic reticulum and removed or chemically permeabilized outer sarcolemma. In skinned fibres, the SR K+ conductance can be effectively reduced with SR K+ channel blockers such as 4-aminopyridine, tetraethylammonium and decamethonium. Interestingly, these blockers increase Ca2+ loading as well as Ca2+ release, whereas other less specific blockers, such as 1.10-bis-quanidino-n-decane, seem to reduce Ca2+ release, possibly also via blocking Ca2+ release channels. Thus, it seems very important also to test the effects of counter-currents carried by K+, Mg2+, H+ or Cl- ions on intact and voltage-clamped single-fibre preparations.